BENTUK-BENTUK PENERAPAN NORMA HUKUM ADAT DALAM KEHIDUPAN MASYARAKAT DI JAWA TENGAH - Sutrisno Purwohadi Mulyono (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2013)
The existence of customary law in the life of central java people has existed for a long time, the rules of law that accommodate and legalize have been there and stratified from the beginning to the level of the basic law to the operation of the rules. Reseach problem: How is the customary forms the rule of law in the life of Central Java people? Research aim, to find out the application forms of customary law in the life of Central Java people. Research kind is policy research. Research type is empirical juridic research. The research characteristic is descriptive with purposive and stratified sampling approach. Primar and secondary data use interview and document. The research method is analytical qualitative. The research result shows, the existence of customary law in the implementation in the people life has existed for a long time. However, there are diversity forms in its application, some directly and some indirectly, depending on the characteristics of the place and time where it is applied. Suggestion, The need for unity indigenous manifested in village administration in order to facilitate social interaction between citizens, in the diversity and protection against right indigenous people.Keywords: Application Forms, Akad, Customary Law, People Life.